Evaluation of leukocyturia among suspected urinary tract infection patients - Sabrina Sabrina (Science Midwifery, 2025)
Urinary tract infections (UTIs) remain a major global health concern and frequently present in primary care, yet epidemiological data on urinalysis markersÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Âparticularly leukocyturia and hematuriaÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Âare limited in community-based clinics. This gap reduces diagnostic accuracy because most existing evidence originates from hospital settings. This study aimed to determine the prevalence and characteristics of leukocyturia among suspected UTI patients and to analyze its association with hematuria in a community outpatient clinic. A retrospective cross-sectional study was conducted using medical records from the Ibnu Sina Clinic, Balikpapan, Indonesia, from January to June 2025. All patients meeting the inclusion criteria were analyzed using descriptive statistics and comparative tests in SPSS version 25. Among 87 eligible patients, most were elderly women, with high urine specific gravity and normal urinary pH. Leukocyturia was predominantly mild-to-moderate (6ÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“20 leukocytes/HPF), and diabetes mellitus emerged as the most frequent comorbidity. A significant association was found between leukocyturia and hematuria (p < 0.05), indicating that increasing inflammatory burden corresponds with greater red blood cell presence in urine. In conclusion, leukocyturia prevalence was highest among elderly diabetic women in this community-based setting. Routine urinalysis remains essential for early infection detection where urine culture is not readily accessible. Future research should incorporate urine culture and antimicrobial resistance testing to enhance diagnostic precision.